2017
DOI: 10.1002/cncr.30849
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors affect the selection of proton radiation therapy for children

Abstract: Socioeconomic factors affect the use of proton radiotherapy in children. Whether this disparity is related to differences in the referral patterns, the knowledge of treatment modalities, or the ability to travel for therapy needs to be further clarified. Improving access to proton therapy in underserved pediatric populations is essential. Cancer 2017;123:4048-56. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 35 publications
2
62
0
Order By: Relevance
“…For instance, it has been shown that access to private insurance compared to Medicaid or no insurance positively affects the prognosis of adult glioblastoma patients leading to better overall survival 4 . While less studied in the pediatric population, data exist demonstrating disparities of care and survival in pediatric oncology patients based on socioeconomic and racial/ethnic factors [5][6][7] . In the U.S., malignant neoplasms are the leading cause of death by disease in children past infancy.…”
mentioning
confidence: 99%
“…For instance, it has been shown that access to private insurance compared to Medicaid or no insurance positively affects the prognosis of adult glioblastoma patients leading to better overall survival 4 . While less studied in the pediatric population, data exist demonstrating disparities of care and survival in pediatric oncology patients based on socioeconomic and racial/ethnic factors [5][6][7] . In the U.S., malignant neoplasms are the leading cause of death by disease in children past infancy.…”
mentioning
confidence: 99%
“…8 However, previous research has also identified differences in treatment utilization across racial-ethnic and socioeconomics groups. [11][12][13] This may be compounded when therapies are novel, intensive, or expensive.…”
Section: Discussionmentioning
confidence: 99%
“…In China, it was estimated that intensity‐modulated photon therapy costs two times than 125 I IBT. Shen et al analyzed 12 101 children in the National Cancer Data Base who had been diagnosed with a solid malignancy and had received photon‐ or proton‐based radiotherapy, and they found that a higher median household income and educational attainment were associated with increased proton use . More than half of this cohort were from rural China; they are struggling to be economically stable due to the children's disease.…”
Section: Discussionmentioning
confidence: 99%